If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 7 = 11 + -7x Reorder the terms: 7 + 2x = 11 + -7x Solving 7 + 2x = 11 + -7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '7x' to each side of the equation. 7 + 2x + 7x = 11 + -7x + 7x Combine like terms: 2x + 7x = 9x 7 + 9x = 11 + -7x + 7x Combine like terms: -7x + 7x = 0 7 + 9x = 11 + 0 7 + 9x = 11 Add '-7' to each side of the equation. 7 + -7 + 9x = 11 + -7 Combine like terms: 7 + -7 = 0 0 + 9x = 11 + -7 9x = 11 + -7 Combine like terms: 11 + -7 = 4 9x = 4 Divide each side by '9'. x = 0.4444444444 Simplifying x = 0.4444444444
| -12x=3 | | 7x+11=11x+12 | | 50x^2+200=0 | | 3x-12/6+x/30=x/5-1 | | 12x+18=2(6x+3) | | 9x=8(3x+5) | | 5/7(x+1)=1/21(x+6) | | -4=(-4m+9+m)3-13 | | 4x+9=47/5+3x | | 14x^3+(3x+8x^3)= | | 9x^2+270=0 | | 94-5x=13x+16 | | 16x-(3x-7)=12 | | -5/6x+1=5/18 | | 3y+12=3(4+y) | | -(-5+5p)+6p=-8 | | 8=15-c/3 | | y=7-(1) | | y=7-(0) | | 3p-1=5(9-1) | | 21-7b=-4+5(8b+5) | | y=7-(-1) | | 4(3x-6)=24 | | 6-10x=56-24x | | .5(12x-4)+6=14-10x | | y=-3(3) | | 2(6x-6)=72 | | 14x-(9x-3)=30 | | 1/2*9/2 | | 2ab+4a= | | 7(8+4x)=364 | | 4u=70-3u |